2019
DOI: 10.21203/rs.2.230/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sedative use of Dexmedetomidine vs. Propofol after Cardiac Surgery: A critical review and meta-analysis.

Abstract: Background : The use of dexmedetomidine for sedation post-cardiac surgery is controversial compared to the use of propofol. Methods : A computerized search on Medline, EMBASE, Web of Science, and Agency for Healthcare Research and Quality databases was performed for up to July 2019. Trials evaluating the efficacy of dexmedetomidine versus propofol in the postoperative sedation of cardiac surgery patients were selected. Primary study outcomes were classified as time-dependent (mechanical ventilation time; time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The patients in our study represent a sample of more severely ill patients, they were diagnosed with sepsis requiring IMV. In addition, previous studies have reported that no significant differences were found in the length of ICU stay, duration of mechanical ventilation, and cardiovascular adverse events associated with dexmedetomidine between the different ICU types (Pereira et al, 2020;Abowali et al, 2021;Heybati et al, 2022). We hypothesized that non-SICU patients may have other underlying comorbidities that influence the effects of dexmedetomidine.…”
Section: Discussionmentioning
confidence: 86%
“…The patients in our study represent a sample of more severely ill patients, they were diagnosed with sepsis requiring IMV. In addition, previous studies have reported that no significant differences were found in the length of ICU stay, duration of mechanical ventilation, and cardiovascular adverse events associated with dexmedetomidine between the different ICU types (Pereira et al, 2020;Abowali et al, 2021;Heybati et al, 2022). We hypothesized that non-SICU patients may have other underlying comorbidities that influence the effects of dexmedetomidine.…”
Section: Discussionmentioning
confidence: 86%